Perovskite thin film and preparation method and application thereof
By using ferrocene passivation of Sn-based or Sn-Pb-based perovskite layers in perovskite solar cells, the problem of easy oxidation of divalent tin ions is solved, and the efficiency and stability of solar cells are improved.
Patent Information
- Application Number
- CN202411728633.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The efficiency of existing pure tin-based or tin-lead-based perovskite solar cells is generally not high and their stability is poor. It is mainly because divalent tin ions are prone to oxidation into tetravalent tin ions, resulting in a shorter carrier life.
Ferrocene is used as the passivation material, and a hole transport layer, a Sn-based or Sn-Pb-based perovskite layer and a ferrocene layer are stacked in sequence to form a passivation perovskite film, effectively inhibiting the oxidation of Sn2+.
It improves the efficiency and stability of pure tin-based or tin-lead-based perovskite solar cells, extends the carrier life and improves the photoelectric performance.
Smart Images

Figure CN119677307A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photoelectric thin film materials, and in particular to a perovskite thin film and a preparation method and application thereof. Background Art
[0002] Solar energy is a new energy source with great development potential. Among them, perovskite, as a light-absorbing material for the new generation of photovoltaic devices, has attracted much attention. High-efficiency solar cells are mainly pure lead-based perovskite materials. However, lead-containing compounds are harmful to both the human body and the ecological environment. The raw materials used to prepare pure lead-based perovskites and the lead-containing compounds in the prepared photovoltaic devices can cause death if leaked into the human body, and can cause ecological damage if leaked into the natural environment. Currently, researchers are looking for tin, a substance that can replace lead, to prepare pure tin or tin-lead-based perovskites, in order to reduce harm to the human body and pollution to the environment.
[0003] However, divalent tin ions are easily oxidized to tetravalent tin ions when exposed to oxygen, resulting in P-type doping and shortened carrier lifetime, making the current pure tin-based or tin-lead-based perovskite solar cells generally not efficient and having poor stability.
[0004] Therefore, it is necessary to provide a solution to improve the efficiency and stability of pure tin-based or tin-lead-based perovskite solar cells. Summary of the invention
[0005] In view of this, the present application provides a perovskite film and a preparation method and application thereof, which are used to solve the problem of how to improve the efficiency and stability of pure tin-based or tin-lead-based perovskite solar cells.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a passivated perovskite film, which includes a hole transport layer, a Sn-based or Sn-Pb-based perovskite layer, and a ferrocene layer stacked in sequence, wherein the ferrocene-based perovskite film layer is passivated.
[0007] Preferably, the system of the Sn-based or Sn-Pb-based perovskite layer is FA x MA 1-x Pb y Sn 1-y I3, where 0.7≤x≤0.9, 0≤y≤0.5.
[0008] Preferably, x=0.7, y=0.5.
[0009] In a second aspect, the present application provides a method for preparing a passivated perovskite film, comprising the following steps: S1. Spin-coating the hole transport layer material on the ITO glass substrate and performing annealing treatment to form a hole transport layer on the ITO glass substrate; S2. Spin-coating the perovskite precursor solution on the surface of the hole transport layer and adding an anti-solvent for annealing and crystallization, thereby forming a Sn-based or Sn-Pb-based perovskite layer on the surface of the hole transport layer; S3. Spin-coat the ferrocene solution onto the surface of the Sn-based or Sn-Pb-based perovskite layer and perform annealing to obtain a passivated perovskite film.
[0010] Preferably, the perovskite precursor solution is obtained by dissolving a perovskite raw material in an organic solvent and then oscillating the solution, the perovskite raw material includes one or more of formamidine iodide, methyl iodide, lead iodide, and stannous iodide, and the organic solvent is a mixture of DMF and DMSO, preferably the ratio of DMF to DMSO is 3:1.
[0011] Preferably, the ferrocene solution is a chlorobenzene solution of ferrocene, and the concentration of the chlorobenzene solution of ferrocene is 0.5-1.0 mg / ml.
[0012] Preferably, in step S1, the annealing temperature is 130-150° C., and the annealing time is 10-20 min.
[0013] Preferably, in step S2, the anti-solvent is chlorobenzene; Preferably, in step S2, the annealing temperature is 100-120° C., and the annealing time is 30-40 min.
[0014] Preferably, in step S3, the deposition method is a wet deposition method such as spin coating, spray coating, etc., preferably spin coating, the spin coating speed is 4000-7000 rpm / min, more preferably dynamic spin coating, the dynamic spin coating speed is 5000-6000 rpm / min.
[0015] Preferably, in step S3, the annealing temperature is 70-100° C. and the annealing time is 5-10 min, which preferably further improves the uniformity of the ferrocene layer.
[0016] In a third aspect, the present application provides a perovskite solar cell device comprising a passivated perovskite film.
[0017] The beneficial effects of the present application are as follows: The present application uses organic metal ferrocene as a passivation material to passivate Sn-based or Sn-Pb-based perovskite films, which makes up for the Sn in pure tin or tin-lead-based perovskite films. 2+ Easily oxidized to Sn 4+ The shortcomings of the method are overcome, and the efficiency and stability of pure tin-based or tin-lead-based perovskite solar cells are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 XRD diagrams of the perovskite films obtained in Example 1 and Comparative Example 1; Figure 2 The photoluminescence spectra of the perovskite films obtained in Example 1 and Comparative Example 1; Figure 3 The XPS spectra of the perovskite films obtained in Example 1 and Comparative Example 1; Figure 4 JV curves of the perovskite solar cell devices prepared in Example 2 and Comparative Example 2. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The present invention is further described below by means of specific embodiments.
[0021] The present application provides a passivated perovskite film, which includes a hole transport layer, a Sn-based or Sn-Pb-based perovskite layer, and a ferrocene layer stacked in sequence.
[0022] The hole transport layer includes but is not limited to a PEDOT:PSS film.
[0023] In this application, the system of Sn-based or Sn-Pb-based perovskite layer is FA x MA 1-x Pb y Sn 1-y I3, where 0.7≤x≤0.9, 0≤y≤0.5.
[0024] It is worth noting that methylamine ion is one of the commonly used organic cations. It is moderately sized and can be stably embedded in the perovskite lattice, which is crucial to maintaining the stability of the structure. However, if the ratio is greater than 0.3, the stability improvement effect is poor and the photoelectric performance of the device is greatly affected. Therefore, x=0.7 is selected. Since tin has lower toxicity than lead, it has more advantages in terms of environmental protection and health. However, if the proportion of tin exceeds 0.5, the efficiency of the device will drop significantly, so y=0.5 is selected. Therefore, when the system FA of the Sn-Pb-based perovskite layer x MA 1-x Pb y Sn 1-y I3, x=0.7, y=0.5, that is, when the molar ratio of formamidine iodide (FAI), methylamine iodide (MAI), lead iodide (PbI2), and stannous iodide (SnI2) is 0.7:0.3:0.5:0.5, the device has good photoelectric performance and the lead content is the lowest.
[0025] The present application provides a method for preparing a passivated perovskite film, comprising the following steps: S1. Spin-coating the hole transport layer material on the ITO glass substrate and performing annealing treatment to form a hole transport layer on the ITO glass substrate; S2. Spin-coating the perovskite precursor solution on the surface of the hole transport layer and adding an anti-solvent for annealing and crystallization, thereby forming a Sn-based or Sn-Pb-based perovskite layer on the surface of the hole transport layer; S3. Spin-coat the ferrocene solution onto the surface of the Sn-based or Sn-Pb-based perovskite layer and perform annealing to obtain a passivated perovskite film.
[0026] The perovskite precursor solution is obtained by dissolving the perovskite raw material in an organic solvent and then shaking it, the frequency of the shaking is 200 times / min, and the shaking time is 3-4h; the perovskite raw material includes one or more of methyl iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride, and the organic solvent is a mixture of DMF and DMSO. In some embodiments, the volume ratio of DMF to DMSO is 3:1-2. When the perovskite raw material contains both tin and lead elements, the perovskite precursor solution is a tin-lead based solution, and when the perovskite raw material is lead-free, the perovskite precursor solution is a pure tin based solution.
[0027] In some embodiments, before spin coating the hole transport layer (PEDOT:PSS film), the ITO glass substrate is cleaned with ultrapure water, detergent, and ethanol in sequence, and then dried and UV treated.
[0028] The solution of ferrocene is a chlorobenzene solution of ferrocene, and the concentration of the chlorobenzene solution of ferrocene is 0.5-1.0 mg / ml. Ferrocene is added to chlorobenzene and fully shaken to dissolve, thereby obtaining the chlorobenzene solution of ferrocene.
[0029] In step S1, the annealing temperature is 150-200° C., the annealing time is 10-20 min, and the annealing is followed by natural cooling.
[0030] In step S2, the annealing temperature is 100-120°C, the annealing time is 30-40 minutes, and the annealing is followed by natural cooling.
[0031] In step S2, the anti-solvent includes chlorobenzene; the timing of adding the anti-solvent is 20-25 seconds before the end of spin coating of the perovskite precursor solution, and the amount of the anti-solvent added is 120-150 μL.
[0032] In step S3, the spin coating is performed by dynamic spin coating at a speed of 5000-6000 rpm / min for 30-35 seconds.
[0033] In step S3, the annealing temperature is 100-150° C., and the annealing time is 2-3 minutes.
[0034] The present application provides a perovskite solar cell device comprising a passivated perovskite film.
[0035] The present solution is further described below through specific embodiments.
[0036] Example 1 A method for preparing a passivated perovskite film comprises the following steps: S1. The ITO glass substrate is cleaned with ultrapure water, detergent, and ethanol in sequence, blown dry and then treated with UV, and then PEDOT:PSS is spin-coated on the ITO glass substrate, and annealed at 150°C for 5 min to obtain an ITO glass substrate covered with a PEDOT:PSS film as a hole transport layer; S2. Mix methyl iodide (FAI), methyl iodide (MAI), lead iodide (PbI2), and stannous iodide (SnI2) in a molar ratio of 0.7:0.3:0.5:0.5, add them into a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 3:1), and oscillate at 200 times / min for 3 hours to form a perovskite precursor solution. Spin the perovskite precursor solution on the surface of the PEDOT:PSS film at 5000 rpm and add 120 μL of anti-solvent chlorobenzene 20 seconds before the end of spin coating, and then anneal at 100 °C for 10 minutes. After natural cooling, a Sn-Pb-based perovskite layer (FAI) is formed on the surface of the PEDOT:PSS film. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3); S3. Spin-coat a 0.5 mg / ml ferrocene chlorobenzene solution onto the surface of the Sn-Pb-based perovskite layer at 5000 rpm for 20 seconds, then anneal at 100 °C for 2 minutes and cool naturally to obtain a passivated perovskite film.
[0037] The passivation perovskite film of this embodiment includes a PEDOT:PSS film, a Sn-Pb-based perovskite layer, and a ferrocene layer stacked in sequence.
[0038] Example 2 A perovskite solar cell device comprising a passivated perovskite film, the preparation method being as follows: The ITO glass substrate was cleaned with ultrapure water, detergent, and ethanol in sequence, dried and then treated with UV light, and then PEDOT:PSS was spin-coated on the ITO glass substrate and annealed at 150°C for 5 min to obtain an ITO glass substrate covered with a PEDOT:PSS film as a hole transport layer. Methyl iodide (FAI), methyl iodide (MAI), lead iodide (PbI2), and stannous iodide (SnI2) were mixed in a molar ratio of 0.7:0.3:0.5:0.5, and then added into a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO was 3:1), and oscillated at 200 times / min for 3 hours to prepare a perovskite precursor solution. The perovskite precursor solution was spin-coated on the surface of the PEDOT:PSS film at 5000 rpm and 120 μL of the anti-solvent chlorobenzene was added 20 seconds before the end of the spin coating, and then annealed at 100°C for 10 minutes. After natural cooling, a Sn-Pb-based perovskite layer (FAI) was formed on the surface of the PEDOT:PSS film. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3); A 0.5 mg / ml ferrocene chlorobenzene solution was spin-coated onto the surface of the Sn-Pb-based perovskite layer at 5000 rpm for 20 seconds, and then annealed at 100° C. for 2 minutes and cooled naturally to obtain a passivated perovskite film.
[0039] The obtained passivated perovskite film was transferred to an evaporator, and 20nm C60, 7nm BCP and 100nm Ag electrode were sequentially evaporated to obtain a perovskite solar cell device.
[0040] Embodiment 3-7 A method for preparing a passivated perovskite film, the other contents are the same as those of Example 2, except that the concentrations of the ferrocene chlorobenzene solution are 0, 0.3, 1, 1.5, and 2 mg / ml, respectively.
[0041] Comparative Example 1 A method for preparing a perovskite film comprises the following steps: The ITO glass substrate was cleaned with ultrapure water, detergent, and ethanol in sequence, dried and then treated with UV light, and then PEDOT:PSS was spin-coated on the ITO glass substrate and annealed at 150°C for 5 min to obtain an ITO glass substrate covered with a PEDOT:PSS film as a hole transport layer. Methyl iodide (FAI), methylamine iodide (MAI), lead iodide (PbI2), and stannous iodide (SnI2) are mixed in a molar ratio of 0.7:0.3:0.5:0.5, and then added into a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 3:1), and oscillated at 200 times / min for 3 hours to prepare a perovskite precursor solution. The perovskite precursor solution is spin-coated on the surface of the PEDOT:PSS film at 5000 rpm and 120 μL of anti-solvent chlorobenzene is added 20 seconds before the end of spin coating, followed by annealing at 100°C for 10 minutes. After natural cooling, a Sn-Pb-based perovskite layer is formed on the surface of the PEDOT:PSS film, which is a perovskite film.
[0042] Comparative Example 2 A perovskite solar cell device comprising a perovskite film, wherein the preparation method thereof is as follows: The ITO glass substrate was cleaned with ultrapure water, detergent, and ethanol in sequence, dried and then treated with UV light, and then PEDOT:PSS was spin-coated on the ITO glass substrate and annealed at 150°C for 5 min to obtain an ITO glass substrate covered with a PEDOT:PSS film as a hole transport layer. Methyl iodide (FAI), methylamine iodide (MAI), lead iodide (PbI2), and stannous iodide (SnI2) are mixed in a molar ratio of 0.7:0.3:0.5:0.5, and added into a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 3:1), and oscillated at 200 times / min for 3 hours to prepare a perovskite precursor solution. The perovskite precursor solution is spin-coated on the surface of the PEDOT:PSS film at 5000 rpm and 120 μL of anti-solvent chlorobenzene is added 20 seconds before the end of spin coating, and then annealed at 100°C for 10 minutes. After natural cooling, a Sn-Pb-based perovskite layer is formed on the surface of the PEDOT:PSS film, which is a perovskite film.
[0043] The obtained perovskite film was transferred to an evaporator, and 20nm C60, 7nm BCP and 100nm Ag electrode were sequentially evaporated to obtain a perovskite solar cell device.
[0044] Test and Evaluation The XRD patterns of the perovskite films obtained in Example 1 and Comparative Example 1 were tested, and the results were as follows: Figure 1 The photoluminescence spectra of the two perovskite films are shown in Figure 2 The X-ray photoelectron (XPs) spectra of the two perovskite films are shown in Figure 3As shown. XRD-XRD patterns were recorded with a D8 Advance X-ray diffractometer. XPS patterns were detected using an X-ray photoelectron spectrometer (ThermoFischer, ESCALAB Xi), and the binding energy was calibrated using C1 s (284.8 eV) as a reference. XPS-XPS patterns were detected using an X-ray photoelectron spectrometer (Thermo Fischer, ESCALAB Xi), and the binding energy was calibrated using C1 s (284.8 eV) as a reference. PL-Steady-state PL spectra were examined using a PL microspectrometer (Flex One, Zolix, China), while fluorescence lifetime from a Delta Flex system (Horiba Scientific Com., Japan) was used.
[0045] The JV curves of the perovskite solar cell devices obtained in Example 2 and Comparative Example 2 are tested, and the results are as follows: Figure 4 As shown, the open circuit voltage (Voc), fill factor (FF), short circuit current (Jsc), and cell efficiency (PCE) of the perovskite solar cell devices obtained in Example 2 and Comparative Example 2 were tested, wherein the current density-voltage (JV) curve of the device was measured using a Keithley 2400 source meter in an indoor environment (≈25°C, ≈25% RH). The light source used was a solar simulator (Oriel 94 023 A, 300 W) matching AM 1.5G, and the light intensity was set to 100 mW cm -2 , calibrated by a standard silicon reference solar cell (Oriel, VLSI Standards). All devices were tested using a ferrous metal aperture, with a specified active area of 0.058 cm for small size devices 2 The results are shown in Table 1, where Fs represents forward scanning and Rs represents reverse scanning.
[0046] Table 1 Performance test results of perovskite solar cell devices
[0047] Depend on Figure 1 It can be seen that the use of ferrocene for passivation has no effect on the perovskite crystal structure and orientation, and will not cause crystal segregation. Figure 2 It can be seen that the main peak intensity of the perovskite film of Example 1 after ferrocene passivation is significantly greater than that of the perovskite film of Comparative Example 1, indicating that the non-radiative recombination defects are effectively reduced after passivation. Figure 3 It can be seen that the Sn in the perovskite of Example 1 after ferrocene passivation 4+ The content of Sn 2+ The content increased, indicating that the Sn 2+ Oxidized to Sn4+ .
[0048] Figure 4 The JV curves of the perovskite solar cell devices prepared in Example 2 and Comparative Example 2 are combined with Table 1, and it can be seen that the open circuit voltage (Voc) and fill factor (FF) after passivation are significantly improved. The forward and reverse scan efficiencies of the perovskite solar cell device that has not been passivated are 16.27% (PCE of the cell efficiency of the forward scan Fs of Comparative Example 2) and 15.83% (PCE of the cell efficiency of the reverse scan Rs of Comparative Example 2), respectively, which are increased to 19.11% and 19.09% after passivation.
[0049] Through a large number of studies, it was found that due to the strong electron donation ability of the π orbital in the cyclopentadiene in Fc, it effectively inhibited the Sn 2+ Oxidation of Sn-Pb mixed perovskite by introducing a ferrocene covering layer on the surface can maintain a reducing environment, reduce the defect density, and improve the carrier lifetime, thereby greatly improving the photoelectric performance of Sn-Pb based perovskite photovoltaic devices.
[0050] The passivation effect of the perovskite film obtained using ferrocene solutions of different concentrations was tested. The results are shown in Table 2, which shows that the passivation effect is best when the ferrocene solution is 0.5 mg / ml, and the photoelectric performance of the device is improved the most.
[0051] Table 2 Test results using different concentrations of passivation solvents
[0052] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A perovskite film, characterized in that: The invention comprises a hole transport layer, a Sn-based or Sn-Pb-based perovskite layer and a ferrocene layer which are stacked in sequence.
2. The perovskite film according to claim 1, characterized in that The system of the Sn-based or Sn-Pb-based perovskite layer is FA x MA 1-x Pb y Sn 1-y I3, where 0.7≤x≤0.9, 0≤y≤0.
5.
3. A method for preparing a perovskite film according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Spin-coating the hole transport layer material on the ITO glass substrate and performing annealing treatment to form a hole transport layer on the ITO glass substrate; S2. Spin-coating the perovskite precursor solution on the surface of the hole transport layer and adding an anti-solvent for annealing and crystallization, thereby forming a Sn-based or Sn-Pb-based perovskite layer on the surface of the hole transport layer; S3. Spin-coat the ferrocene solution onto the surface of the Sn-based or Sn-Pb-based perovskite layer and perform annealing to obtain a passivated perovskite film.
4. The method for preparing a perovskite thin film according to claim 3, characterized in that: The perovskite precursor solution is obtained by dissolving a perovskite raw material in an organic solvent. The perovskite raw material includes one or more of formamidine iodide, methyl iodide, lead iodide, and stannous iodide. The organic solvent should be one or more of DMF, DMSO, and NMP.
5. The method for preparing a perovskite thin film according to claim 3, characterized in that: The ferrocene is dissolved in an organic solvent, and the organic solvent is one or a mixed solvent of chlorobenzene, ethyl acetate, and isopropanol.
6. The method for preparing a perovskite thin film according to claim 3, characterized in that: In step S1, the annealing temperature is 120-200°C, and the annealing time is 10-30 minutes.
7. The method for preparing a perovskite thin film according to claim 3, characterized in that: In step S2, the anti-solvent is one of chlorobenzene and ethyl acetate; the annealing temperature is 100-150° C., and the annealing time is 20-50 min.
8. The method for preparing a perovskite thin film according to claim 3, characterized in that: In step S3, the deposition method is spin coating, and the rotation speed of the spin coating is 3000-8000 rpm / min.
9. The method for preparing a perovskite thin film according to claim 3, characterized in that: In step S3, the annealing temperature is 70-150° C., and the annealing time is 2-10 min.
10. A perovskite solar cell device, characterized in that: Comprising the perovskite film according to any one of claims 1 to 2.
Citation Information
Patent Citations
Perovskite solar cell prepared based on Fc anti-solvent engineering and preparation method
CN118829258A
Passivator, passivation method therefor and method for preparing semiconductor film
WO2020248864A1